The pallet project - Nina Tolstrup (Oz, 2010)
Engaging in issues of sustainability, and how I make a difference as a designer, is very important for the way I run and develop my studio. How can I use design as agent for social change and empowering local communities? The Pallet Project takes this philosophy to a newly interactive conclusion.